Additive effects of Pityrogramma calomelanos L. (link.) combinated with aminoglycosides against Staphylococcus aureus - Teógenes M. Souza; Maria F.B.M. Braga; José G.M Costa; Antônio A.F. Saraiva; Henrique D.M. Coutinho (International Journal of Phytomedicine, 2012)
This study is the first report about the enhancement of additive effect of Pityrogramma calomelanos L. (link) associated with aminoglycosides against a multiresistant Staphylococcus aureus. In this study, the ethanol extract and the ethyl acetate fraction were assayed to identify the relationship between these natural products and the aminoglycosides using the checkerboard method. The checkerboard assay was realized to verify if the relationship between these drugs and natural products represent a synergistic, additive, indifferent or antagonistic effect. All natural products and antibiotics assayed demonstratetd an additive effect, with FIC index = 0.5. These results indicate that the ethanol extract and the ethyl acetate fraction of P. calomelanos can be a source of plant derived products with antibiotic modifier activity, affecting positively the antibiotic activity of aminoglycosides.